PEMBINAAN MANAJEMEN ONLINE MARKETING UNTUK MENINGKATKAN JUMLAH PENDAFTAR SEKOLAH SELFA - Vivin Zulfa Atina; Alfina Indah Rahmawati; Aisyah Aisyah (Jurnal Abdi Insani, 2022)
In this digitalization era, the marketing world continues to grow rapidly, marketing strategy is the most important part because it is directly related to the company's goals to be achieved. Marketing management is an effort to plan, implement, supervise marketing activities within an organization so that its objectives are achieved effectively and efficiently. Digital marketing strategies will help marketers to analyze consumers and make decisions based on information obtained from consumers directly (No Title, n.d.). Marketing about early childhood education is still rarely done, this should not happen, because early childhood education is very important to shape children's character (Harahap, 2021). The purpose of this coaching service program in general is to describe the impact of digital marketing on marketing volume for Sayf El Falah KB & TK schools, to help promote and socialize the importance of early childhood education. The interview process that we conducted was in the type of qualitative data collection, using content and discourse analysis methods to obtain information directly from KB&TK SELFA. The coaching system that we do is by visiting the SELFA KB & TK and conducting interviews with the teacher's mother. In general terms for the results we obtained during the coaching process, we have been successful in achieving the expected goals. The goals we mean are in the form of a description of the impact of digital marketing on marketing volume for SELFA KB & TK schools, and promoting SELFA KB & TK, as well as socializing the importance of early childhood education. In addition, the implied goal of the results of the training so far is to be able to provide information directly to consumers. The direct information we mean is in the form of a real picture on the video about the teaching and learning process at SELFA KB & TK.